Workplace Stressors and the Intention to Quit: The Role of Psychological Distress and Psychological Flexibility Among Hospitality Employees - Asier Baquero; Hazem Ahmed Khairy; Bassam Samir Al-Romeedy (Tourism and Hospitality, 2025)
This study investigates how workplace stressors influence the intention to quit among male employees working in five-star hotels in Egypt, with a focus on the mediating role of psychological distress and the moderating role of psychological flexibility. A cross-sectional survey was conducted with 334 full-time male hospitality workers. Using partial least squares structural equation modeling (PLS-SEM), the study examined the relationships between workplace stressors, psychological distress, the intention to quit, and psychological flexibility. The results showed that higher levels of workplace stressors were significantly associated with increased psychological distress and a stronger intention to quit. Psychological distress partially explained (mediated) the link between stressors and quitting intentions. Moreover, psychological flexibility acted as a buffer (moderator), reducing the negative impact of workplace stress on distress and, in turn, on quitting intentions. These findings highlight the unique contribution of the study in applying the transactional model of stress and coping within a Middle Eastern hospitality context, focusing exclusively on male workers—an understudied group in the existing literature. To address these challenges, hospitality managers are encouraged to adopt evidence-based interventions such as mindfulness-based stress reduction (MBSR) and acceptance and commitment therapy (ACT) to strengthen employees’ psychological flexibility and reduce the turnover risk. The study offers valuable insights for researchers, organizational leaders, and HR practitioners aiming to improve employee well-being and retention in high-pressure service environments.